Penggunaan Media Chromebook dalam Pembelajaran PAI dan Budi Pekerti di SMP Kaur Utara Provinsi Bengkulu - Jonsi Oktinan Toni (UIN Fatmawati Sukarno Bengkulu, 2023)
The objectives of the research are: (1) Analyzing the learning planning for the use of chromebook media in learning Islamic Religious Education and morals in North Kaur Region Middle School, Bengkulu Province. (2) Analyzing the implementation of learning using chromebook learning media in learning Islamic Religious Education and morals in junior high school. North Kaur Region, Bengkulu Province. (3) Analyzing the learning evaluation of the use of chromebook learning media in learning Islamic religious education and character at North Kaur Regional Middle School, Bengkulu Province. Type of descriptive qualitative research. Informant Principal or deputy principal Teachers and Students Research results: (1) Planning for the use of chromebook media in PAI and Character learning at North Kaur Middle School has carried out planning for the use of chromebook media starting with the procurement of chromebook media by identifying learning needs by the school , then preparing learning objectives, materials and learning plans that are appropriate to the use of Chromebook media. (2) The implementation of using Chromebook media in PAI and Budi Character learning has gone well, which is based on the implementation stages that have been carried out, such as the pre-instructional phase for PAI and Budi teachers. Pekerti explains the use of chromebook media so that students can understand how to use this media. The instructional stage at this stage carries out core learning activities such as using project based learning methods. Then the post-instructional stage at this stage is the final activity in learning and as material for teacher evaluation in using chromebook media. (3) Evaluation of the use of chromebook media in PAI and Character learning at SMP in the North Kaur region has a positive impact on the implementation of the use of chromebook media in the learning process. This cromebook media can develop students' skills in technology, ethics and creativity in the context of learning Islamic religious education. One of the evaluations carried out by PAI and Budi Pekerti teachers is by asking students directly after learning has taken place.